Biodiversity and natural product diversity - Pietra, Francesco, 1933- (Tetrahedron organic chemistry series, 2002)
This, the most recent contribution to the Tetrahedron Organic Chemistry series, provides an integrated evaluation of the diversity of natural products in relation to biodiversity. The ongoing exploitation of biological resources, while maintaining an effective equilibrium on Earth, depends much on the conservation of biodiversity. To this end, parts one and two focus on biodiversity from all viewpoints, while explaining the link with natural products. The third section concentrates on the molecular-shape level, as a link to ecosystem and biodiversity, while the fourth section tackles actual fu.